Переслідування антисергієвської опозиції в РПЦ: з історії «істинно-православної церкви» (1932–1941 рр.) - Тригуб, О. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2007)
Based on the unknown documents, the process of pursuit of the followers of «The genuine Orthodox Church» by the state security service was investigated.